How many cases of laryngopharyngeal reflux suspected by laryngoscopy are gastroesophageal reflux disease-related? - de Bortoli, Nicola (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the prevalence of gastroesophageal reflux disease (GERD) in patients with a laryngoscopic diagnosis of laryngopharyngeal reflux (LPR). METHODS: Between May 2011 and October 2011, 41 consecutive patients with laryngopharyngeal symptoms (LPS) and laryngoscopic diagnosis of LPR were empirically treated with proton pump inhibitors (PPIs) for at least 8 wk, and the therapeutic outcome was assessed through validated questionnaires (GERD impact scale, GIS; visual analogue scale, VAS). LPR diagnosis was performed by ear, nose and throat specialists using the reflux finding score (RFS) and reflux symptom index (RSI). After a 16-d wash-out from PPIs, all patients underwent an upper endoscopy, stationary esophageal manometry, 24-h multichannel intraluminal impedance and pH (MII-pH) esophageal monitoring. A positive correlation between LPR diagnosis and GERD was supposed based on the presence of esophagitis (ERD), pathological acid exposure time (AET) in the absence of esophageal erosions (NERD), and a positive correlation between symptoms and refluxes (hypersensitive esophagus, HE). RESULTS: The male/female ratio was 0.52 (14/27), the mean age ± SD was 51.5 ± 12.7 years, and the mean body mass index was 25.7 ± 3.4 kg/m(2). All subjects reported one or more LPS. Twenty-five out of 41 patients also had typical GERD symptoms (heartburn and/or regurgitation). The most frequent laryngoscopic findings were posterior laryngeal hyperemia (38/41), linear indentation in the medial edge of the vocal fold (31/41), vocal fold nodules (6/41) and diffuse infraglottic oedema (25/41). The GIS analysis showed that 10/41 patients reported symptom relief with PPI therapy (P < 0.05); conversely, 23/41 did not report any clinical improvement. At the same time, the VAS analysis showed a significant reduction in typical GERD symptoms after PPI therapy (P < 0.001). A significant reduction in LPS symptoms. On the other hand, such result was not recorded for LPS. Esophagitis was detected in 2/41 patients, and ineffective esophageal motility was found in 3/41 patients. The MII-pH analysis showed an abnormal AET in 5/41 patients (2 ERD and 3 NERD); 11/41 patients had a normal AET and a positive association between symptoms and refluxes (HE), and 25/41 patients had a normal AET and a negative association between symptoms and refluxes (no GERD patients). It is noteworthy that HE patients had a positive association with typical GERD-related symptoms. Gas refluxes were found more frequently in patients with globus (29.7 ± 3.6) and hoarseness (21.5 ± 7.4) than in patients with heartburn or regurgitation (7.8 ± 6.2). Gas refluxes were positively associated with extra-esophageal symptoms (P < 0.05). Overall, no differences were found among the three groups of patients in terms of the frequency of laryngeal signs. The proximal reflux was abnormal in patients with ERD/NERD only. The differences observed by means of MII-pH analysis among the three subgroups of patients (ERD/NERD, HE, no GERD) were not demonstrated with the RSI and RFS. Moreover, only the number of gas refluxes was found to have a significant association with the RFS (P = 0.028 and P = 0.026, nominal and numerical correlation, respectively). CONCLUSION: MII-pH analysis confirmed GERD diagnosis in less than 40% of patients with previous diagnosis of LPR, most likely because of the low specificity of the laryngoscopic findings.